2007
DOI: 10.1097/hjh.0b013e3281139ea9
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease severity is related to high levels of C-reactive protein in pre-eclampsia

Abstract: These findings suggest that chronic periodontitis may increase hs-CRP levels in pregnant women and lead to complications such as pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 41 publications
(44 reference statements)
2
54
0
3
Order By: Relevance
“…Differences between developed countries in the causes of preeclampsia and in the strategies to prevent it have been described [123]. Inflammation secondary to vaginal and urinary subclinical infection [124,125], periodontal disease [126], insulin resistance [127] are considered as possible risk factors for the development of preeclampsia. Therefore, it is important that pregnant women with the above-mentioned risk factors be carefully followed to detect hypertension and proteinuria early, prevent severe complications requiring hospitalization, and, if necessary, perform cesarean delivery to preserve mother and child.…”
Section: Definition and Classificationmentioning
confidence: 99%
“…Differences between developed countries in the causes of preeclampsia and in the strategies to prevent it have been described [123]. Inflammation secondary to vaginal and urinary subclinical infection [124,125], periodontal disease [126], insulin resistance [127] are considered as possible risk factors for the development of preeclampsia. Therefore, it is important that pregnant women with the above-mentioned risk factors be carefully followed to detect hypertension and proteinuria early, prevent severe complications requiring hospitalization, and, if necessary, perform cesarean delivery to preserve mother and child.…”
Section: Definition and Classificationmentioning
confidence: 99%
“…The same is true for serum high-sensitivity C-reactive protein concentration, in the general population as well as in some specific populations. [3][4][5][6] According to Ross and Glomset's theory, 7,8 inflammation is responsible for the development of atherosclerosis. It was found that markers of inflammation (e.g., high-sensitivity C-reactive protein) are predictors of cardiovascular mortality and morbidity in the general population.…”
mentioning
confidence: 99%
“…For example, mothers with severe periodontal disease have been reported to be at high risk of premature delivery, low-weight babies 4,16,18,20,24,[27][28][29][30][31][32][33][34] , and preeclampsia 5,6,13,18,35) . Meanwhile, periodontal bacteria have been shown to cause heart disease 3,12,21) in adults.…”
Section: Introductionmentioning
confidence: 99%